Pattern of head injuries in the recent megaearthquakes in Nepal: an audit to prepare for future! - Renu Vaidhya (Society of Surgeons of Nepal, 2016)
Introduction and Objective: Nepal falls in very high risk zone for earthquakes. Recently in April 2015, we witnessed the worst human casualty of this century. We present an audit of the head injuries we received at KMCTH during the Mega-earthquake.